A 3D perspective on sediment accumulation in algal turfs: Implications of coral reef flattening. (18th July 2019) - Tebbett, Sterling B.; Streit, Robert P.; Bellwood, David R.
Abstract: Globally, coral reefs are being transformed by a suite of stressors, the foremost being climate change. Increasingly, it is expected that these reconfigured reef systems will emerge with lower‐complexity and will be dominated by algal turfs. Understanding this new operating space is vital if we are to maintain the services, such as fishable biomass production, that reefs provide. However, the functionality of these systems appears to depend on the nature of the algal turfs themselves, which is in‐turn, intimately linked to the sediments they contain. As reefs are losing complexity, we need to understand if, and to what extent, algal turf condition and complex reef structure are connected. To address this issue we took advantage of recent developments in 3D structure‐from‐motion technology to examine how complexity metrics (elevation and surface angle) related to the nature of algal turfs on a heavily climate‐impacted coral reef. This represents a novel application of this technology in the context of coral reef ecosystems. We found that as both elevation and surface angle decreased, the nutritional value of the epilithic algal matrix also decreased while sediment accumulation increased. Furthermore, we showed that elevated surfaces were characterized by far shorter algal turfs, and are potentially herbivory hotspots, offering fertile grounds for further exploration of herbivory dynamics at sub‐metre spatial scales. Synthesis. This study yields new insights into the operating‐space of future reefs, and suggests that as reefs flatten, sediment accumulation is likely to increase even if sediment inputs remain unchanged, altering algal turfs fundamentally. Maintaining key services provided by climate‐transformed, low‐complexity algal turf‐dominated reefs of the future, will depend on managing the complex interactions between herbivory, sediments, algal turfs and reef structural complexity. Abstract : We took advantage of recent developments in 3D structure‐from‐motion technology to examine how topographic complexity related to the nature of algal turfs on a coral reef. Our results suggest that as reefs flatten, sediment accumulation in algal turfs will be enhanced, altering algal turfs, and the ecosystem processes they are involved in, fundamentally.